Range of Motion in Segmental Versus Nonsegmental Ultrahigh Molecular Weight Polyethylene Sublaminar Wire Growth Guidance Type Constructs for Early-Onset Scoliosis Correction. Issue 23 (December 2015) - Roth, Alex K.; van der Veen, Albert J.; Bogie, Rob; Willems, Paul C.; van Rietbergen, Bert; van Rhijn, Lodewijk W.; Arts, Jacobus J.
Abstract : Study Design: An in vitro biomechanical study in porcine thoracic spine segments comparing range of motion (ROM) in segmental versus multiple nonsegmental ultrahigh molecular weight polyethylene (UHMWPE) sublaminar wire constructs. Objective: To determine the effect of varying instrumentation (wire) density in an UHMWPE sublaminar wire construct for patients with early-onset scoliosis (EOS) to find an optimal wire density, which allows maximum growth whereas still providing adequate correction and fixation. Summary of Background Data: UHMWPE sublaminar wires in a segmental construct did not negatively affect longitudinal spinal growth during a 24-week period in an ovine model; application in growth guidance system for EOS may therefore be feasible. To avoid ectopic bone formation as much as possible, a reduction of instrumented levels, without affecting spinal stabilization, is desirable. Methods: ROM of 9 porcine thoracic spines (T6–T14) was determined in flexion/extension (FE), lateral bending (LB), and axial rotation up to ± 4 Nm. Tests were performed for the uninstrumented spine in a segmental construct with UHMWPE sublaminar wires and dual pedicle screws at the most caudal level, and in four nonsegmental constructs that were attained by stepwise removal of the most caudal wire. Results: Segmental instrumentation led to a decrease in total ROM by approximately 70% for both FE and LB. A stepwise increase in ROM with decreasing number of consecutively instrumented levels was most clearly observed in LB. However, consistent significant but also relevant substantial differences in ROM for both FE and LB were noted only when comparing two and one consecutively instrumented end levels ( P < 0.05). Conclusion: A construct with two consecutive end levels instrumented with UHMWPE sublaminar wires seems to provide the best balance between spinal stabilization and minimizing the number of instrumented levels and thereby surgical exposure, which is crucial for allowing longitudinal growth. Level of Evidence: N/A